Biopsychosocial Factors on Infertility among Men in Surakarta, Central Java - Agustina, Devita; Budihastuti, Uki Retno; Murti, Bhisma (Indonesian Journal of Medicine, 2018)
Background: Impaired fertility affects 717% of all couples. Isolated male factor infertility may occur in 20% of all infertile couples. One recent study demonstrated a high rate of erectile dysfunction, depressive symptoms, and dysfunctional sexual relationships among male partners of infertile couples. This study aimed to examine the biopsychosocial factors on infertility among men in Surakarta, Central Java.Subjects and Method: This was a cross-sectional study conducted at Sekar Clinic (Infertility Clinic), Dr. Moewardi Hospital, Surakarta, Central Java, from January to May 2018. A sample of 120 men was selected by fixed disease sampling. The dependent variable was infertility. The independent variables were age, body mass index (BMI), smoking, occupational radiation exposure, stress, and physical activity. Data on infertility were obtained from medical record. The other variables were measured by questionnaire. The data were analyzed by path analysis run on Stata 13.Results: Male infertility was directly and positively associated with age ?40 years (b=1.45; 95% CI= 0.34 to 2.49; p=0.010), BMI ?25 (b=0.98; 95% CI= -0.95 to 2.05; p=0.074), smoking (b=0.98; 95% CI= 0.57 to 1.91; p= 0.037), occupational radiation exposure (b=1.63; 95% CI= 0.52 to 2.75; p=0.004), and lack of physical activity (b=1.11; 95% CI= 0.13 to 2.09; p=0.027). Male infertility was indirectly associated with stress.Conclusion: Male infertility is directly and positively associated with age ?40 years, BMI ?25, smoking, occupational radiation exposure, and lack of physical activity. Male infertility is indirectly associated with stress.Keywords: infertility, male, smoking, body mass index, occupational radiation exposure, path analysisCorrespondence:Devita Agustina. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami No. 36 A, Surakarta 57126, Central Java. Email: inidevita@gmail.com.Indonesian Journal of Medicine (2018), 3(1): 226-233https://doi.org/10.26911/theijmed.2018.03.01.02